Sleep disorder as a predisposing factor to obesity (One Health & Risk Management, 2021)
Introduction. The modern humans today are loaded with many activities such as traffic congestion, stressful jobs, time spent on social networks and other activities that take up time and energy, so that sleep and rational nutrition have come to be considered a waste of time. The modern humans can no longer afford to "waste time" sleeping or preparing healthy food. Some studies have shown that those who sleep little, less than 5-6 hours a night are 45% more likely to become obese. Fatigue caused by insomnia has a major impact on metabolism, affecting the production of leptin, which is responsible for the feeling of satiety. Thus, the craving for carbohydrates will increase due to the low level of leptin, according to research, respectively increases the risk of obesity. People who sleep little tend to skip main meals and tend to eat between meals, select high-calorie foods, which promotes weight gain.Material and methods. The study was performed at the University Clinic of Primary Health Care of Nicolae Testemitanu State University of Medicine and Pharmacy, based on the addressability of patients diagnosed with obesity, during 2020. The research was outlined in a cross-sectional descriptive study, which included interviewing based on the questionnaire about sleep disorders and publications from specialized sources. This present study used bibliographical, observational, description, statistical, nutritional methods etc. Based on the informed consent for the study, 112 females participated, diagnosed with obesity in association with sleep disorders, aged between 50 and 59 years, which served as criteria for inclusion in the study.Results. The assessment of body mass index (BMI) values ​​showed that out of 112 participants, 81 (72.32%) cases had BMI ≥30 kg/m2, 26 (23.21%) BMI ≥35 kg/m2 and BMI ≥40 kg/m2 was determined in 5 (4.46%) people. The mean body weight increase at the time of the patient's determination of the phenomenon was 6.0±0.20 kilograms per year. Out of 112 people included in the study, 74 (66.07%) people complained of sleep disorders before becoming obese, stress being the common cause. Of which 25 (33.78%) persons reported intermittent sleep with periodic awakenings from 3-5 times a night, 17 (22.97%) of respondents had difficulty with falling a sleep, shallow sleep – 12 (16.22%) and other trubules of sleep the 20 (27.03%).  From participants 59 (79.72%) complained of multiple sleep disorders. 20 (27.02%) respondents with sleep disorders reported eating during the night.Conclusions. Reduced sleep duration and stressful conditions are common problems of modern societies, which along with unhealthy consumption of high-calorie foods at inappropriate times have led to weight gain. To reduce obesity, a sleep duration.